2015
DOI: 10.1002/cbic.201500164
|View full text |Cite
|
Sign up to set email alerts
|

A Light‐Controlled TLR4 Agonist and Selectable Activation of Cell Subpopulations

Abstract: Spatial and temporal aspects of immune cell signalling are key parameters in defining the magnitude of an immune response. Toll-like receptors (TLRs) on innate immune cells are important in early detection of pathogens and initiation of an immune response. Controlling the spatial and temporal signalling of TLRs would enable further study of immune synergies and assist in the development of new vaccines. Here, we show a light-based method for spatial control of TLR4 signalling. A TLR4 agonist, pyrimido[5,4-b]in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…13 In addition, the indole nitrogen has been functionalized with nitroveratryloxycarbonyl (NVOC) to afford a light-activated TLR4 agonist, showing that this site is important for ligand binding despite docking studies suggesting it may be solvent accessible. 108 More recently, a further optimized pyramido- [5,4-b]indole TLR4 agonist (Compound 26, EC 50 : 600 nM, Fig. 4B) was shown to improve and bias human TLR4 activation over mouse TLR4 activation.…”
Section: ø Tlr4mentioning
confidence: 99%
“…13 In addition, the indole nitrogen has been functionalized with nitroveratryloxycarbonyl (NVOC) to afford a light-activated TLR4 agonist, showing that this site is important for ligand binding despite docking studies suggesting it may be solvent accessible. 108 More recently, a further optimized pyramido- [5,4-b]indole TLR4 agonist (Compound 26, EC 50 : 600 nM, Fig. 4B) was shown to improve and bias human TLR4 activation over mouse TLR4 activation.…”
Section: ø Tlr4mentioning
confidence: 99%
“…The fast response of endocytosis after illumination indicated that the behavior of the cells could be temporally controlled using the photocaged TLR8 model. The spatial control of TLR can also be measured by detecting the behavior of downstream NF‐κB [5d] . To test spatial constraints, we measured nuclear translocation of the p65 subunit of NF‐κB by stimulating a portion of the cells in a 20‐mm diameter well by using a 5‐mm diameter circular photo‐mask.…”
Section: Figurementioning
confidence: 99%
“…Microfluidic delivery is complementary to existing methods for local stimulation of intact lymphoid tissue. For instance, light-induced stimulation of photo-activated receptors 11,12,52 and release of caged molecules 53,54 offer potentially higher spatial and temporal resolution than fluidic delivery, but require genetically modified animals 55 or specifically designed cage systems for each molecule of interest. Microinjection is another well-established approach for local stimulation in brain 13,56 , although it may increase the risk of local tissue damage around the insertion site.…”
Section: Local Activation Of Immune Cells On-chipmentioning
confidence: 99%